Effects Of Hot-Spot Temperature, Microstructure And BaA12O4 Addition On Oxygen Sensing Properties Of REBa2CU3O7-δ(RE=Er, Dy) Ceramic Rods / Misbah Hassan - Hassan, Misbah (Institute of Graduate Studies, UiTM, 2012)
Oxygen sensing properties of REBa2Cu3O7-d-based (RE123, RE = Er and Dy) ceramics utilizing the hot spot phenomenon have been investigated. Although shorter rods of around 12 mm are more practical for industrial use compared to previously reported rods longer than 30 mm, their oxygen sensing properties have not been previously reported. Bulk 123 materials were synthesized using the conventional solid-state method and fabricated into short rods of around 12-mm length with cross sectional area of 0.65 mm ´ 0.65 mm. In the first part of this study, influence of hot-spot temperature in the range of 160 °C to 810 °C on oxygen sensing behavior of Er123 rods was studied. Simultaneous measurements of hot-spot temperature and output current response in different oxygen partial pressures between 1 % and 100 % with hot-spots operating at temperatures as low as 660 °C in 1 % oxygen partial pressure produced good sensor current stability as well as repeatability. Response time for oxygen sensing was observed to decrease with increasing hot-spot temperature, with minimum value of 0.50 s recorded at 695 °C in 1 % oxygen partial pressure.